Pengembangan Lembar Kerja Siswa (LKS) Dengan Pendekatan Project Based Learning (PjBL)Pembuatan Batu Merah Dalam Materi IPAS Gaya dan Gerak Pada Siswa Kelas IV SD Inpres Wailiti Maumere - Maria Delcen Paji; Sonya Kristiani Maria; Yoanita Dewi Roswita Kolo; Marianus Yufrinalis (Journal on Education, 2024)
This study aims to develop Student Worksheets (LKS) through the application of the Project-Based Learning model of Red Stone Making. The material developed is the subject of Social Natural Sciences (IPAS) with the material Force and Motion. This research occurred on grade IV students of SD Negeri Wailiti Maumere which amounted to 25 people. The results showed that the development of LKS with a Project-Based Learning approach to making red bricks of force and motion materials in grade IV SD Negeri Wailiti has been successfully developed through research procedures based on the R&D development model, and refers to several stages of 4D development, namely define, design, develop and disseminate, which is carried out only to the third stage. LKS validation is carried out by means of validation tests of media experts and material experts, and product trials. The effectiveness of LKS is shown at the field implementation test stage by filling out a questionnaire by sisswa. LKS with this Project-Based Learning approach received student assessments and responses that were included in the "Very Good" category with a score of 99.5. Based on the results of the data above, LKS with a Project-Based Learning approach is "Very Feasible" to be used as one of the learning resources for students in schools, especially in science subjects style and motion material for grade IV students of SD Negeri Wailiti.